IMPLEMENTASI LAYANAN INFORMASI DALAM BIMBINGAN KLASIKAL UNTUK MENINGKATKAN KONSENTRASI BELAJAR PADA SISWA KELAS V DI MI NURUS SHOFA KUDUS - Meisya Nanik Anggriyana; Eka Puji Fitriani; Dwi Maharani; Annisa Aulia Salsabila; Ade Sucipto (Jurnal Prasasti Ilmu, 2026)
The purpose of this study was to understand the learning concentration of fifth-grade MI students in the context of classical guidance services. This study used a qualitative method with data collection through a questionnaire distributed to 29 students. The questionnaire aims to measure students' attention to the teacher, focus while studying, concentration disorders, and student interest during teaching and learning activities. The findings of this study indicate that student concentration is quite good. The majority of students managed to pay attention and listen to the teacher's explanation well and were able to focus when completing assignments. However, there are several factors that hinder student concentration, such as being easily distracted by friends, feeling bored during learning, playing while the teacher is explaining, and difficulty understanding the material being taught. Therefore, classical tutoring services are considered very important to help students improve their concentration by providing understanding, motivation, and focus training during the learning process.